معايرة تربونين I بعد احتشاء العضلة القلبية الحاد وعلاقته بالجزء المقذوف للبطين الأيسر - جحجاح, أكرم; رضوان, عبد الناصر; حسن, حسين (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة في قسم الأمراض الباطنة لمشفى الأسد الجامعي في اللاذقية خلال العام 2008-2009، والهدف من هذه الدراسة هو تحديد العلاقة بين مستوى التربونين I والجزء المقذوف للبطين الأيسر،وشملت الدراسة 30 حالة لديهم احتشاء عضلة قلبية حاد مع ارتفاع ثابت بوصلة ST ،أجري لهم معايرة التربونين I بطريقة الإليزا وتمت حساب الجزء المقذوف للبطين الأيسر بإجراء إيكو للقلب حسب قانون سيمبسون المعدل ،لاحظنا أن هناك علاقة عكسية بين مستوى التربونين I في المصل و الجزء المقذوف للبطين الايسر (r=-0.90, p<0.0001) ،أي انه مع ازدياد مستوى تربونين I في المصل هناك انخفاض في قيمة الجزء المقذوف للبطين الأيسر. This study was carried out in the Department of Internal Medicine at AL-ASSAD University Hospital in Lattakia during the year 2008-2009. The aim of this study was to determine the relation of serum troponin I after ST elevation acute myocardial infarction to left ventricular ejection fraction. This study included 30 patients with acute myocardial infarction; serum torponin I concentration was measured by ELISA method, and echocardiographic ejection fraction was calculated by modified SIMPSON's rule. There was a strong negative correlation between serum torponin I concentration and left ventricular ejection fraction (r=-0.90, p<0.0001); as serum torponin I levels increased, LV ejection fraction fell.